The Cuban-American agreement and the diplomacy of Pope Francis (Comillas Journal of International Relations, 2017)
The agreement between Cuba and the United States in late December 2014 where the resumption of relations between the two countries was agreed, after more than fifty years of interruption shows, a historic change and a reciprocal opportunity. This article analyzes the bilateral relations in political-historical terms and then review the events leading up to the agreement given that this involved a complex negotiation and effort of a number of heterogeneous actors. Between this different actors, the article highlights the performance of Pope Francisco who enabled the agreement and acted as a bridge builder between Obama and Raúl Castro. Finally, we introduce and analize the still controversial issues between them.
Keywords: Cuba; United States; agreement; negotiations; Pope Francis; goals achieved